2018
DOI: 10.1016/j.ygeno.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology of total knee arthroplasty instability defined by RNA-seq

Abstract: Total knee arthroplasty (TKA) is a durable and reliable procedure to alleviate pain and improve joint function. However, failures related to flexion instability sometimes occur. The goal of this study was to define biological differences between tissues from patients with and without flexion instability of the knee after TKA. Human knee joint capsule tissues were collected at the time of primary or revision TKAs and analyzed by RT-qPCR and RNA-seq, revealing novel patterns of differential gene expression betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Patients with metal-on-cement disease present primarily with chronic diffuse knee pain, buckling, and difficulty in walking; thus, a broad subset of etiologies must be considered [3, 7]. The differential diagnoses are a chronic low-grade PJI, instability, aseptic loosening of components from polyethylene wear, implant misalignment, inflammatory joint disease, metal allergy, chronic pain syndrome from a chronic connective tissue disorder, local neoplastic process, or insufficiency fractures [2, 9]. MARS MRI or metal ion levels are not done routinely in knees due to the nature of metal on polyethylene articulation but are important as it will help diagnose hidden etiologies for implant failure, as seen here.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with metal-on-cement disease present primarily with chronic diffuse knee pain, buckling, and difficulty in walking; thus, a broad subset of etiologies must be considered [3, 7]. The differential diagnoses are a chronic low-grade PJI, instability, aseptic loosening of components from polyethylene wear, implant misalignment, inflammatory joint disease, metal allergy, chronic pain syndrome from a chronic connective tissue disorder, local neoplastic process, or insufficiency fractures [2, 9]. MARS MRI or metal ion levels are not done routinely in knees due to the nature of metal on polyethylene articulation but are important as it will help diagnose hidden etiologies for implant failure, as seen here.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Excessive release of the medial ligament, inadequate distal femoral resection, excessive tibial slope, internal rotation of components and an undersized femoral component can also lead to flexion instability. 38 41 A study by Lewallen et al 42 showed increased extracellular matrix (ECM) remodelling gene expression in TKR patients with flexion instability and also suggested a correlation between ECM degradation and exposure of oxidative stress during tissue remodelling and inflammation.…”
Section: Instabilitymentioning
confidence: 99%